Microfinance And Empowerment: A Case Study On Beneficiaries Of A Community Development Program (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the current era, for developing countries, empowerment as a mechanism for poverty alleviation, is becoming a challenge. Poverty alleviation requires a shift from a traditional “top-down” approach to a “bottom-up” approach. This can be done by building capacity within the communities. Considering the importance of the bottom-up approach a microfinance institution started its activities in a small village under the scheme of a community development program for getting sustainable empowerment. In order to explore the change that has occurred because of microfinance, provided under the scheme of a community development program, a qualitative study has been conducted. For data collection, two focus groups were conducted over the community development program. The findings revealed that beneficiaries experienced four different phases of empowerment; sensitization, intervention, initiating empowerment, and sustainable empowerment.